2016
DOI: 10.1016/j.funeco.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Mutualism with aggressive wood-degrading Flavodon ambrosius (Polyporales) facilitates niche expansion and communal social structure in Ambrosiophilus ambrosia beetles

Abstract: 2016-11-03T14:11:40

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 44 publications
3
46
1
Order By: Relevance
“…By comparison, farming in ants and termites has evolved only once despite their undoubtedly intimate contact with various fungi in their environment. In stark contrast to ambrosia beetles (excluding Austroplatypus and perhaps some Ambrosiophilus species) (Kasson et al., ), farming ants and termites are eusocial and form large, well‐defended, colonies to the exclusion of other insect species. This social structure likely impedes the comingling of cultivars and behaviour in a common substrate with other nonfarming, mycophagous species (Mueller et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…By comparison, farming in ants and termites has evolved only once despite their undoubtedly intimate contact with various fungi in their environment. In stark contrast to ambrosia beetles (excluding Austroplatypus and perhaps some Ambrosiophilus species) (Kasson et al., ), farming ants and termites are eusocial and form large, well‐defended, colonies to the exclusion of other insect species. This social structure likely impedes the comingling of cultivars and behaviour in a common substrate with other nonfarming, mycophagous species (Mueller et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In the 50 My following PETM radiations, at least 14 lineages evolved. As existing farmers domesticated new fungal lineages (Kasson et al., , ; Mayers et al., ), an asynchrony between the age of the beetle's farming habit and the time of domestication for fungal lineages is observed. An example of this asynchrony is the Scolytine genus Gnathotrichus which did not evolve a farming habit until 16–34 Ma (95% credibility crown node, Gohli et al., ) despite its association with R. gnathotrichi , a very close relative of R. arxii , a lineage whose ancestor was domesticated ~86 Ma (Figure A).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, ambrosia beetles’ mycosymbionts are not limited to the ascomycetous Ophiostomatales . Li et al (2015) found a new basidiomycetous Polyporales fungus, Flavodon ambrosius (Simmons et al 2016), in symbiosis with Ambrosiodmus species, and Kasson et al (2016) found the same mycosymbiont associated with another genus, Ambrosiophilus , which is sister to Ambrosiodmus (Hulcr & Cognato 2010). Thus, as investigations into these insects increase in number, additional fungal genera in unexpected lineages may be found in symbioses with ambrosia beetles.…”
Section: Discussionmentioning
confidence: 99%